Improving Thai EFL secondary school students’ English literacy and thinking skills through CEFR-based digital storytelling - Tachom, Khomkrit; Narueprempree, Nipawan; Mungthaisong, Sornchai (Edelweiss Applied Science and Technology, 2025)
CEFR-Based Digital Storytelling plays a crucial role in promoting EFL students' literacy and thinking skills. This study aimed to investigate the effects of CEFR-Based Digital Storytelling on students' English literacy and thinking skills. The participants included 48 secondary school students studying at a public university demonstration school in northern Thailand during the second semester of the 2024 academic year. The participants were randomly divided into experimental and control groups, with 24 students in each group. The instruments used included pre- and post-tests utilizing Bloom's revised taxonomy to assess the students' English literacy and thinking skills. The statistical analysis was conducted using the Mann-Whitney U test. The results indicated that the post-test reading skills scores of the experimental group were significantly higher than those of the control group. Regarding thinking skills, the post-test scores for basic order thinking skills of the experimental group were not significantly higher than those of the control group. However, the post-test scores for higher-order thinking skills of the experimental group were higher than those of the control group. The findings of this study suggest that CEFR-Based Digital Storytelling is valuable and applicable for enhancing EFL students' English literacy and thinking skills.